Urolithin A and B Derivatives as ON-OFF Selective Fluorescent Sensors for Iron(III) - Fallah, Amirhossein; Noshadi, Bahareh; Gazi, Mustafa; Gulcan, Hayrettin Ozan (Springer/Plenum Publishers, 2020)
The detection and sensing of environmentally crucial metal ions has always been of great significance in various fields such as biological and environmental cycles. Our previous studies have indicated a new coumarin based lactone, Urolithin B (i.e., 3-Hydroxy[c]chromen-6-one) as a potent fluorescent probe for the selective detection of Iron (III). In order to question the extension of this application to other urolithins, we have synthesized the major urolithins that humans are exposed to through regular diet. Following the structure identifying studies, the compounds were tested in fluorescence titration to investigate their interaction with various metals. The results have indicated that each title compound is selective to interact with Iron (III) in ON-OFF mode, independent from the presence of another metal. Similar to the previous findings, the Job's plots displaying the ratio of complex formation 3:2 UROs:Fe3+ have indicated the significance of the lactone group solely.
Keywords: Urolithin A & B; Iron (III); Chemo-sensor; Fluorescence probe